If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 3x + 27 Reorder the terms: 12 = 27 + 3x Solving 12 = 27 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 12 + -3x = 27 + 3x + -3x Combine like terms: 3x + -3x = 0 12 + -3x = 27 + 0 12 + -3x = 27 Add '-12' to each side of the equation. 12 + -12 + -3x = 27 + -12 Combine like terms: 12 + -12 = 0 0 + -3x = 27 + -12 -3x = 27 + -12 Combine like terms: 27 + -12 = 15 -3x = 15 Divide each side by '-3'. x = -5 Simplifying x = -5
| 45=3x+7 | | 3(3n-1)=(4n+2)+8 | | 16x^2+30x-x^3=6x-9-x^3 | | -1+(-3)=x | | 6x+28=-9x-2 | | 4+20x-20=5-10x+5 | | 7t-4=10t-14 | | 15=2y-12 | | 5x+6-12x=-12 | | -14-8=e | | 35+35+x=180 | | 5-(3n-4)=3(n+2) | | 6a-2(a-3)=-12 | | 19=-3k-5 | | 4(1)-7y=15 | | 3x-4=2-4 | | 3(x+7)+2=2x+2(3x-1) | | 7p-36=-4(-6p-8) | | 6-4+5*11= | | -2u^2-7u-5=0 | | -3(5-b)= | | 2(-2x+4)=-8 | | 4x^3+13x^2+4x-12=0 | | -6x+7x+6=18 | | 2(+3)+4s-5+s=148 | | 4(5+4)-10=2(9+f)-6 | | 12x-4=5x+66 | | 4(x+5)-6=6x-2(-5+x) | | 4(4-t)-(3-2t)=9 | | 75x+150=-3 | | -8x-136=4x+80 | | 3.2y-1.33=-y+4.13 |